Efficacy of prothrombin complex concentrates for the emergency reversal of dabigatran-induced anticoagulation. Issue 1 (December 2016) - Grottke, Oliver; Aisenberg, James; Bernstein, Richard; Goldstein, Patrick; Huisman, Menno; Jamieson, Dara; Levy, Jerrold; Pollack, Charles; Spyropoulos, Alex; Steiner, Thorsten; del Zoppo, Gregory; Eikelboom, John
Abstract Dabigatran is effective in decreasing the risk of ischaemic stroke in patients with atrial fibrillation. However, like all anticoagulants, it is associated with a risk of bleeding. In cases of trauma or emergency surgery, emergency reversal of dabigatran-induced anticoagulation may be required. A specific reversal agent for dabigatran, idarucizumab, has been approved by the US Food and Drug Administration. Alternative reversal agents are available, such as prothrombin complex concentrates (PCCs) and activated PCCs (aPCCs). In this review we evaluate the role of PCCs and aPCCs in the reversal of dabigatran anticoagulation and consider which tests are appropriate for monitoring coagulation in this setting. Pre-clinical studies, small clinical studies and case reports indicate that PCCs and aPCCs may be able to reverse dabigatran-induced anticoagulation in a dose-dependent manner. However, dosing based on coagulation parameters can be difficult because available assays may not provide adequate sensitivity and specificity for measuring anticoagulation induced by dabigatran or the countering effects of PCCs/aPCCs. In addition, PCCs or aPCCs can potentially provoke thromboembolic complications. Despite these limitations and the fact that PCCs and aPCCs are not yet licensed for dabigatran reversal, their use appears to be warranted in patients with life-threatening haemorrhage if idarucizumab is not available.